Pathological study on the upper respiratory tract infection of chickens and isolation, identification of causal bacteria (Bangladesh Veterinarian, 2012)
The proportional occurrence of bacteria and pathological lesions in the nasal sinuses and trachea of dead chickens were determined during 2008-2009. Nasal sinus and tracheal swabs from 50 dead birds were collected in sterile nutrient broth. The histopathological samples were collected in 10% neutral buffered formalin and studied with light microscope. The isolation and identification of bacteria were performed by culture, staining and biochemical tests. The proportional occurrence of bacteria in trachea (n = 50) and nasal sinuses (n = 50) of dead chickens was Klebsiella sp. (6.0%), Escherichia coli (38.8%), Pasteurella sp. (8.6%), Bacillus sp. (5.2%) and Staphylococcus sp. (41.4%). Congested trachea (n=3) and mucus-filled sinuses (n = 3) of dead chickens were studied for histopathology. Microscopically, rhinitis was characterized by infiltration of macrophages, lymphocytes and few neutrophils. The epithelium of nasal passage revealed pyknotic nucleus with disruption of epithelium. There was sinusitis with purulent and necrotic changes around the nasal sinus. The nasal sinuses were infiltrated with macrophages, lymphocytes and few plasma cells. The mucosal layer of the nasal turbinates showed pus and necrosis. There was disruption of different mucous glands with accumulation of macrophages, lymphocytes and plasma cells in the submucosa.DOI: http://dx.doi.org/10.3329/bvet.v28i2.10677 Bangl. vet. 2011. Vol. 28, No. 2, 60 69